The Impact of Human Psychological Conditions on the Application of Islamic Law in Determining the Validity of Worship - Abu Bakar Abu Bakar; Muhammad Rifqi Ridho (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2025)
This study aims to analyze the influence of human psychological conditions on the application of Islamic law, focusing on aspects of taklīf, worship, transactions, testimony, and criminal rulings. The research employed a library study (library research) method by reviewing classical Islamic texts, scholarly books, and relevant journal articles. The findings reveal that psychological conditions play a significant role in determining the validity of worship, contracts, and legal judgments, as sound intellect is the primary requirement for legal responsibility (taklīf). Core principles of maqāṣid al-sharī‘ah, such as hifẓ al-‘aql, la ḍarar, and justice, highlight that mental disorders may annul or reduce legal obligations. Furthermore, the mental health of a mujtahid is essential to ensuring the objectivity and validity of ijtihād. These findings affirm that Islamic law is humanistic and adaptive to psychological realities while also providing opportunities for integration between fiqh and psychology in addressing contemporary challenges.